Revolutionary marxist students in Poland speak out (1964-1968) - Kuron, Jacek; Modzelewski, Karol; Zambrowski, Antoni; Deutscher, Isaac (New York : Merit Publishers, 1968)
Bibliotheek François Vercammen
Engels
Brochure
Keywords: marxisten; Polen